A higher Dietary Inflammatory Index score is associated with a higher risk of breast cancer among Chinese women: a case–control study. Issue 10 (5th June 2017) - Huang, Wu-Qing; Mo, Xiong-Fei; Ye, Yan-Bin; Shivappa, Nitin; Lin, Fang-Yu; Huang, Jing; Hébert, James R.; Yan, Bo; Zhang, Cai-Xia
Abstract: Previous studies have investigated the association between dietary inflammatory potential and the development of cancer. For breast cancer the results have been equivocal. The present study aimed to investigate whether higher Dietary Inflammatory Index TM (DII) scores were associated with increased risk of breast cancer among Chinese women. A total of 867 cases and 824 controls were recruited into the present case–control study from September 2011 to February 2016. DII scores were computed based on baseline dietary intake assessed by a validated 81-item FFQ. The OR and 95 % CI were assessed by multivariable logistic regression after adjusting for various potential confounders. DII scores in this study ranged from −5·87 (most anti-inflammatory score) to +5·71 (most proinflammatory score). A higher DII score was associated with a higher breast cancer risk (adjusted ORquartile 4 v . 1 2·28; 95 % CI 1·71, 3·03; adjusted ORcontinuous 1·40; 95 %CI 1·25, 1·39). In stratified analyses, positive associations also were observed except for underweight women or women with either oestrogen receptor+ or progesterone receptor+ status (but not both). Results from this study indicated that higher DII scores, corresponding to more proinflammatory diets, were positively associated with breast cancer risk among Chinese women.